Analisis Strategi Pemasaran Produk Abon Ikan (Suatu Kasus Pada UMKM Citra Permata Kendari) - Nurmaida, Esti Agesta; Tuwo, Muhammad Akib; Surni, Surni (Department of Agribusiness, Halu Oleo University, 2019)
The purpose of the research is to formulate the appropriate marketing strategy through the marketing mix concept involve the owner as of the internal and the consumer as the external parties in the organization. Analytic Hierarchy Process (AHP) was used as the method to solve the problems thought the selection of several priorities. The result showed that the order of marketing mix priority that has been chosen by the internal parties are as follow: Promotion, product, place, and price. Also, the ultimate goal can be determined by several criteria of the marketing mix. Those criteria are bazaar/exhibition, quality, cleanliness and comfort, packaging/serving.